Stress and well-being in teams - Harms, Peter; Chang, Chu-Hsiang (Emerald Publishing, 2024)
Stress and Well-Being in Teams is focused on stress and well-being in the context of teams, focused on how inputs of team processes, such as team compositions, leadership, and broader organizational contexts can serve as antecedents of team members' stress and well-being. This 22nd volume of the Research in Occupational Stress and Well Being series highlights the importance of team processes and outcomes on the stress and well-being of team members and leaders, and how their stress and well-being may have reciprocal effects on the critical team inputs, processes, and outcomes over time. Chapters in this volume cover a range of topics including: How team inputs such as member composition and task characteristics may influence the stress and well-being of members and leaders. How the internal and external contexts in which the teams operate may impact the stress and well-being of both team members and leaders. How team processes such as cohesion, coordination, and collaboration may have reciprocal effects with the stress and well-being of team members and leaders. How teamwork in extreme contexts may be leveraged to inform teamwork in typical organizational settings and vice versa from both conceptual and empirical perspectives. How and when team processes and outcomes related to members' stress and well-being may relate to other team characteristics and processes over time. Methodological issues and considerations for understanding stress and well-being in the team context. How and when team processes and outcomes related to members' stress and well-being may relate to other team characteristics and processes over time. Methodological issues and considerations for understanding stress and well-being in the team context.
Keywords: Teams in the workplace / Psychological aspects; Business & Economics; Strategic Planning; Personnel and human resources management; Business strategy